In Search of the Link Between Due Process and Jurisdiction - Stephen E. Gottlieb (Washington University Law Quarterly, 1983)
The purpose of this Article is to locate the sources of jurisdictional doctrine. A coherent theory of due process ought to help explain and guide the development of jurisdictional doctrine. In fact, the sources of due process analysis pose a challenge for jurisdictional doctrine because they expose both the importance and the irrelevance of jurisdiction to fairness, convenience, and due process. A correlative issue concerns two major consequences of jurisdiction: the privilege of collateral attack and the opportunities for review involved in the constitutionalization of the area. Few of the articulated explanations for the existing limitations on jurisdiction seem to justify those remedies. As the doctrinal bases of jurisdiction are explored, they will also be tested against these consequences of jurisdiction.
Keywords: Jurisdiction; Due process of law